Vaginal myofibroblastoma with glands expressing mammary and prostatic antigens - Wallenfels, I; Chlumská, A (Ceskoslovenska patologie, 2012)
A case of unusual vaginal myofibroblastoma containing glands which expressed mammary and prostatic markers is described. The tumor occurred in 70-year-old woman in the proximal third of the vagina. It showed morphology and immunophenotype typical of so-called cervicovaginal myofibroblastoma. The peripheral zone of the lesion contained a few groups of glands suggesting vaginal adenosis or prostatic-type glands on initial examination. The glands showed a surprising simultaneous expression of mammary markers mammaglobin and GCDFP-15 and prostatic markers prostate-specific antigen (PSA) and prostate-specific acid phosphatase (PSAP). Immunostains for alpha-smooth muscle actin, p63 and CD10 highlighted the myoepithelial cell layer of the glands. The finding indicates that simultaneous use of both mammary and prostatic markers for examination of unusual glandular lesions in the vulvovaginal location can be helpful for an exact diagnosis, and can contribute to better understanding of prostatic and mammary differentiations in the female lower genital tract.
Keywords: membránové transportní proteiny; Humans; Female; Aged; senioři; lidé; Membrane Transport Proteins; Immunohistochemistry; Neoplasms, Muscle Tissue; Mammaglobin B; imunohistochemie; Vaginal Neoplasms; mammaglobin B; transportní proteiny; nádory vaginy; Carrier Proteins; glykoproteiny; mammaglobin A; ženské pohlaví; Glycoproteins; Mammaglobin A; nádory ze svalové tkáně